2021
DOI: 10.1590/fst.08220
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract from Capsicum chinense Jacq. ripe fruits: phenolic compounds, antioxidant activity and development of biodegradable films

Abstract: Capsicum spp. pepper has great economic and social importance in agribusiness worldwide, mainly associated with its high performance in cookery as a spice. This study aimed at determining the chemical profile of the ethanolic extract from Capsicum chinense Jacq. (EECC) ripe fruits by liquid chromatography-mass spectrometry (LC-MS) and at evaluating its antioxidant activity by DPPH, ABTS and FRAP. Besides, biodegradable films were prepared by incorporating EECC into arrowroot biofilms. LC-MS identified 10 pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Studies have found that many plants contain the ingredients which have good activities in antioxidant, anti-inflammatory, anti-tumor and other aspects (Costa et al, 2020;Huang et al, 2020;Santos et al, 2021). Curcumol is a sesquiterpene compound isolated from the zedoary turmeric oil which has long been used as a folk medicine in China for many years (You et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that many plants contain the ingredients which have good activities in antioxidant, anti-inflammatory, anti-tumor and other aspects (Costa et al, 2020;Huang et al, 2020;Santos et al, 2021). Curcumol is a sesquiterpene compound isolated from the zedoary turmeric oil which has long been used as a folk medicine in China for many years (You et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that many plant extracts have good pharmacological effects (Lee et al, 2020;Wu et al, 2020;Santos et al, 2021). As TSPJ are the main active ingredients of Panax japonicus, a common medicinal plant growing in China, this study prepared the TSPJ, and investigated their pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Active starch and gum-based films and coatings were prepared mainly by casting method. Glycerol was the most used plasticizer in the preparation of active coating and films [90][91][92][93][94]. In general, the percentage of bioactive compound or extract in starch and gum-based coatings is low, ranging between 0.03 and 1.20%, and all the extracts and isolated bioactive compounds tested acted at the level of lipidic oxidation and microbiological contamination, preventing food spoilage and increasing its shelf-life.…”
Section: Methods Of Incorporation Phenolic Compounds In Gums and Starch-based Coatings And Filmsmentioning
confidence: 99%
“…In order to solve these problems, synthetic preservatives, such as BHT and BHA, are commonly added to foods in order to prevent lipid oxidation and food spoilage [17,94,[110][111][112]. However, due to the apparent toxic effects of these additives and the search for healthier food products [93], natural compounds such as polyphenols appear as an alternative to synthetic additives [17], serving as a valuable ally in the quality preservation of foods and extending their shelf life [103].…”
Section: Phenolic Compounds Incorporated In Gums and Starches For Preparing Active Filmsmentioning
confidence: 99%
See 1 more Smart Citation